The long road to Antietam : how the Civil War became a revolution - Slotkin, Richard, 1942- (New York : Liveright Publishing Corporation, a division of W.W. Norton & Company, 2012)
In the summer of 1862, after a year of protracted fighting, Abraham Lincoln decided on a radical change of strategy, one that abandoned hope for a compromise peace and committed the nation to all-out war. The centerpiece of that new strategy was the Emancipation Proclamation: an unprecedented use of federal power that would revolutionize Southern society.
Turning point : military stalemate and strategic initiatives : July 1862 -- The Confederate offensive : August 1862 -- The invasion of Maryland : September 2-15, 1862 -- The Battle of Antietam : September 16-18, 1862 -- The revolutionary crisis : September 22-November 7, 1862.
Includes bibliographical references (pages 455-461) and index.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Military leadership; United States. -- President (1861-1865 : Lincoln).; Lincoln, Abraham, -- 1809-1865; Emancipation Proclamation (United States. President (1861-1865 : Lincoln)); Lincoln, Abraham -- 1809-1865; Lincoln, Abraham, -- 1809-1865.; United States. -- President (1861-1865 : Lincoln).; Emancipation Proclamation; Antietam, Battle of, Md., 1862.; HISTORY -- United States -- Civil War Period (1850-1877); Command of troops; Maryland; Schlacht am Antietam; Sezessionskrieg; Amerikaanse burgeroorlog; Slavernij; Emancipatie; Veldslagen; Verenigde Staten; Antietam; Slaget vid Antietam 1862.; Presidenter -- historia; Antietam, Battle of, Md., 1862.; 1862; 1800-talet